Local impacts of federal forest policy changes on Canadian model forests: An institutional capacity perspective. (25th November 2019) - Bullock, Ryan; Reed, Maureen G.
Abstract: Although research in multiparty environmental governance has examined how local actors work together, few have focused how changes in higher order government policy directives affect the capacity of local organizations to implement associated management activities over time. We examine changes in three Canadian Model Forests as federal policy objectives shifted from "sustainable forest management" to "sustaining communities." Specially, we adopt the concept of institutional capacity from planning theory to assess changes in knowledge resources, relational resources, and mobilization potential of Model Forest sites during the shift from the Model Forest Programme to the Forest Communities Programme. Analysis of key documents shows that despite being developed as a top‐down programme, individual sites exhibited an array of responses by drawing on local actors with new skills, political acumen, and relational resources to generate local opportunities. Although overall federal support decreased, Model Forest sites fostered collaborations with new sectors, enabling them to link ideas, resources, and influence in new ways and respond to changes they observed in the local context. Local networks created under a federal programme were able to move forward, shift their organizational identity, change visions, and initiate alternative projects after the programme stopped.